WORK PLACE FLEXIBILITY AND PERFORMANCE OF MEDIA COMPANIES IN ANAMBRA STATE (Journal of the Management Sciences, 2026)
This study investigated the relationship between workplace flexibility and the performance of media companies in Anambra State, Nigeria. The media industry has undergone significant changes driven by technological advancements and evolving consumer preferences, necessitating a reevaluation of traditional organizational structures. The research aimed to explore how flexible work arrangements, specifically job sharing, impact employee satisfaction and organizational performance. A descriptive survey research design was employed, eight media firms were selected from the Senatorial Zone of Anambra State, the Population of the Study is 211, Measures of Central Tendency was used to analyze the data and Pearson Moment Correlations Co-efficient was used to test the hypotheses. Structured questionnaires were distributed among the employees across various media firms. The findings revealed a strong positive correlation (r = 0.973) between job sharing and customer satisfaction, indicating that flexible work arrangements enhance employee engagement and service quality. The study highlighted that inadequate workplace flexibility can lead to reduced job satisfaction and impaired organizational effectiveness. Consequently, the research underscores the importance of implementing comprehensive job-sharing policies to attract and retain talent, improve service delivery, and foster a competitive advantage in the industry. It concluded that workplace flexibility significantly influences overall organizational performance, promoting higher productivity and employee commitment. Recommendations include adopting flexible work practices to cater to the diverse needs of employees and enhance customer satisfaction. This research contributed valuable insights to stakeholders in the media sector, offering a foundation for further studies on workplace flexibility and its implications for employee performance and organizational success.
Keywords: Workplace Flexibility; Job Sharing; Organizational Performance; Employee Satisfaction; Media Industry; Anambra State; Nigeria